Creative Migration: a Western Australian case study of creative artists - Bennett, Dawn (Routledge, 2009)
It is well known that a pilgrimage overseas can be crucial to the career development of specialist creative artists. All too often, however, the pilgrimage becomes a permanent migration. Significantly, the loss of this creative talent is not limited to the national level. The dominance of cities as the centres of Australia's knowledge-based economy leads also to migration of creative artists from regional centres and from smaller cities such as Perth, lessening the potential for those regions to attract and retain creative and innovative people. Given the globalised nature of the cultural industries and the emergence of new technologies, this study of Western Australian creative artists whether migration loss could be repositioned as cultural gain. Initial results suggest that spatial separation due to geographic isolation is particularly problematic for Western Australian creative artists both within the regions and the metropolitan area. Despite participants' strong personal connections with Western Australia, artistic connections were tenuous and artistic involvement was negligible. Implications include the need to actively engage with creative migrants by fostering their continued involvement in the cultural life of cities and regions.